IMPLEMENTASI UNDANG-UNDANG NOMOR 8 TAHUN 2016 TENTANG PENYANDANG DISABILITAS DALAM PERLINDUNGAN DAN PEMENUHAN HAK PENYANDANGDISABILITAS DI KABUPATEN BONE - Nur Paikah (Institut Agama Islam Negeri (IAIN) Bone, 2017)
The preamble of the 1945 Constitution philosophically and constitutionally, based on the basic philosophy of Pancasila and the 1945 Constitution, every citizen has equal opportunity in terms of employment, accessing public facilities, obtaining life and decent living, including for persons with disabilities. Law No. 8 of 2016 on Persons with Disabilities emphasizes that